PELATIHAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI DAN DIGITAL MARKETING PADA USAHA BUMBU MASAKAN NURISFOOD - Sulistiyono, Mulia; Bernadhed, Bernadhed; Sutarni, Sutarni (Jurnal Abdi Insani, 2024)
The use of Information and Communication Technology (ICT) has an important role in increasing the competitiveness of micro, small, and medium enterprises (MSMEs), including Nurisfood, a cooking spice producer in Sleman, Yogyakarta. Despite experiencing rapid growth, Nurisfood still faces several major challenges, such as limitations in accounting systems and digital marketing strategies. This Community Service Activity aims to overcome these problems with web-based Accounting Information Systems (AIS) and Cost Accounting and COGS training and digital marketing strategy training. With this intervention, it is hoped that Nurisfood can improve operational efficiency, expand the market, and increase turnover, so that it can compete in the industrial era 4.0. The approach used is through training activities carried out in four sessions for Accounting Information Systems (AIS) and Cost Accounting including the delivery of concepts and materials, discussions, training in calculating Cost of Goods Sold (COGS), and evaluation while digital marketing training includes digital marketing socialization and product photography training using smartphones. The results obtained are in the form of increased knowledge and skills of partners in managing businesses, as well as the application of more effective technology in daily operational activities in the use of AIS, Cost Accounting and quality product photos.